Microbiological and physicochemical quality of raw milk of Beni Mellal-Khenifra - Nysrine Mannani; Najat Ariri; Abdelali Bitar (National Institute of Public Health - National Institute of Hygiene, 2023)
Background: Milk is a nutritious food for humans, but it is also an ideal growth medium for pathogenic bacteria such as Salmonella, Listeria monocytogenes or Campylobacter spp, which can cause food poisoning. Objective: For this reason, we evaluated the microbiological, physicochemical and hygienic quality of raw milk samples in 9 milk collection centres and cooperatives in the Beni-Mellal Khenifr region before and after the implementation of the quality management system, hazard analysis and critical control points (HACCP). Materials and Method: The microbiological and physico-chemical quality of 184 raw milk samples in 9 milk collection centres and cooperatives in the Beni-Mellal-Khenifra region was evaluated before and after the implementation of the quality management, hazard analysis and critical control points (HACCP) system. Results: The physico-chemical results obtained after the implementation of HACCP revealed that 78% of the samples analysed were below the maximum limits authorised at international level. A pH between 6.6 ±0.11 and 6.8±0.02, an acidity of 15°D, the milk is stable according to the Ramsdell test which is negative at 0.9. The temperature remains within the acceptance range with an average of 6.62 ±0.45°C to 7.7 ±0.36°C and the fat content is between 33 and 45g/ml. We also noted an improvement in the microbiological quality of milk in 81% of collection centres and cooperatives. The level of contamination by total coliforms is from 2.5x104 to 11.5x104 CFU/ml lower than the Moroccan standard (NM 08.0.100) of 1.5x104 CFU/ml to 20.3x104 CFU/ml, the total aerobic mesophilic flora and the psychrotrophs have an average of 2.5x105 germs/ml to 82x105 germs/ml lower than before improvement (12.5x105 germs/ml to 192x105 germs/ml). Conclusion: We can conclude that the work done leads to an improvement and satisfaction of the quality of raw milk compared to the standard after the implementation of HACCP.